The contribution of cultural events to the formation of the cognitive and affective images of a tourist destination - Hernández-Mogollón, José Manuel (2018)
This study aims to assess the influence of cultural events, structural elements and place brand on destinations’ overall image, based on an evaluation of cognitive and affective components of destination image. The conceptual model used in the research evaluates the impact of a set of tangible and intangible elements associated with two cultural events (one religious and one theatrical) on the cognitive and affective components of destinations’ image and, ultimately, on the destinations’ overall image. The events were the 2013 Easter celebrations in Cáceres and the Festival of Classical Theatre in Mérida, which is held annually in Spanish. A total of 611 tourists attending these events were personally questioned at the site of the events during the celebrations. The results show that cultural events serve as promoters of tourism and help to develop destination image, as well as suggesting that cognitive image contributes more to the formation of overall image than affective image. The findings also reveal that structural elements and place brand positively influence both destinations’ cognitive and affective images. The event brand does not seem to influence any dimension of destination image. Since this study addresses only a part of the tourism activities held at two destinations, further research needs to be conducted in different destinations and events to confirm these findings.